Evaluating Sustainable Education Using Eco-Literacy - Rachman Hartono (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2020)
Environmental issues are important to be solved because it would threaten both of the current and future life. It can be done through implementing sustainable education as a process of humanization that produced changes in knowledge-understanding, awareness, and sustainable practices. This study aims to evaluate the implementation of sustainable education by examining the differences in ecological literacy among students of the Faculty of Agriculture, the University of Brawijaya based on their year of submission, study program, place of origin, and sex. Several 419 students participated in this online survey. Ecological literacy was measured using an instrument developed by McGin (2014). Chi-square and t-test were applied to test the differences. Results show that the majority of students are classified to have basic ecological literacy. There is no statistical difference in student's ecological literacy based on their year of enrollment, study program, and place of origin. Only based on sex, the difference exists, where female students have a higher level. Although there are no differences in the implementation of sustainable education on the two study programs, the improvement is still needed to raise the level of students' ecological literacy.